Research resources: the Beckett collection, University of Reading. Issue 2 (2nd July 2016) - Dunne, Joseph
Abstract: This article gives a brief history of the Beckett collection at the University of Reading archive and gives an indication of the scholarly disciplines it is most relevant to.